Study of capacitive load effect preamplifier design using Silvaco Gateway: article / Muhammad Taufiq Hood - Hood, Muhammad Taufiq (2011)
This paper is to study about capacitive load effect of preamplifier design by using Silvaco Gateway. Each capacitive load can carry a specific high cut off frequency to use in any application that needed and there are any changes at frequency and transient response due to the changes of capacitive load value. The data that been taken from the two stage operational amplifier (preamplifier) with various capacitive load (10pF to 100pF) at two difference of temperature 27 and 85 °C. The result will have some suitable value of capacitive load to drive load for future use. The design of this preamplifier is using 0.18µm CMOS technology with +1.8V (VDD) and -1.8V (VSS) supply.